El Excentrico, 1961-11-20 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
November 20, 1961 [20 de noviembre de 1961]. Ano 12, No 3. Cover has a photographs of people attending the Club Cuautemoc's Formal Dance. The headline reads, "Preview of Club Cuauhtemoc's Formal Ball Attendance."